Impact of COVID‐19 on Prescriptions for Controlled Substances for Veterans with Opioid Use Disorder. (15th September 2021) - Myers, Ursula; Bishu, Kinfe; Gauthier‐Wetzel, Holly; Grubaugh, Anouk; Axon, R. Neal; Ana, Elizabeth Santa; Gebregziabher, Mulugeta
Abstract : Research Objective: Veterans with opioid use disorder (OUD) are at significant risk of overdose, unintentional death, and a wide range of negative health‐related consequences. While evidenced‐based treatments for OUD exist, including medications for opioid use disorder (MOUD) like buprenorphine (suboxone), there are a number of barriers preventing veterans from accessing this care. A potential avenue to increase the numbers of veterans who can access high quality mental healthcare such as MOUD is through telemental healthcare using VA Video Connect (VVC). While telehealth can mitigate this access to care issue, the opioid crisis led to the Ryan Haight Act of 2008, which mandates that the first visit with a prescriber of schedule II‐IV controlled substances be conducted in person. However, due to the public health emergency caused by COVID‐19, the in person requirement for controlled substances is temporarily waived. Study Design: The aims of this project were to examine temporal changes in controlled substances from September 2019 – August 2020 (6 months before and after the requirement was waived), to understand the impacts of this waiver for veterans with OUD. Population Studied: We examined prescription information from the VA Corporate Data Warehouse for 42, 579 Veterans diagnosed with OUD (91.6% male, 71% white, 16.8% black, 27% rural dwelling). Principal Findings: During this 12‐month window, 56.6% of the sample were prescribed suboxone, 53.6% were prescribed sedatives, and 13.8% were prescribed anxiolytics. Monthly an average of 33, 323 (SD = 3190) prescriptions were filled, with an average of 1.45 (SD = 0.08) medications prescribed per visit. As expected, the largest dip was seen in April 2020, with only 28, 376 prescriptions filled, with an 1.33 prescriptions written per visit. As of August 2020, the rates for prescriptions for controlled substances had not returned to pre‐COVID levels. Conclusions: These data suggest that while telehealth is a legal option to appropriately prescribe controlled substances, it was not utilized in a way that replicated in person care. Future projects that focus on understanding and addressing barriers providers face when attempting to provide care via telehealth are an important next step. Additionally, there was no dramatic increase in prescriptions for controlled substances as a result of the Ryan Haight waiver. Implications for Policy or Practice: These data support keeping the wavier of in person appointments in the Ryan Haight Act is one useful avenue to help providers to provide access to life saving MOUDs. Primary Funding Source: Department of Veterans Affairs.